The Violent and the Weak: When Dictators Care About Social Contracts - Roland Kirstein; Stefan Voigt (Universität des Saarlandes, Center for the Study of Law and Economics (CSLE), 2000)
This paper explores the conditions under which compliance with a social contract establishes an equilibrium in a society. It is assumed that society consists of two groups, one of which has a comparative advantage in using violence, whereas the other one has a comparative advantage in producing a private good. Violence can be used to produce security as well as to exploit the weaker group. Yet, exploitation is limited: it reduces the incentives of the exploited group to produce the private good and increases the chances of a revolution. A social contract consists of the exchange of security against a share of the private good, produced at a high level of effort. The model not only allows the derivation of conditions for either compliance or exploitation to occur, but also sheds light on the transition from one form of government to the other. Hence, it contributes to Positive Constitutional Economics, i.e., the research program that is interested in explaining the emergence and the change of constitutions. – – Das Paper zeigt die Bedingungen auf, unter denen die Einhaltung eines Sozialvertrages ein Gleichgewicht ist. Dabei wird angenommen, daß die Gesellschaft aus zwei Gruppen besteht: Die eine hat einen komparativen Kostenvorteil bei der Anwendung von Gewalt, die andere beim Herstellen eines privaten Gutes. Gewalt kann sowohl zur Produktion von Sicherheit benutzt werden, als auch zur Ausbeutung der schwächeren Gruppe. Ausbeutung ist jedoch nur begrenzt möglich, weil sie zum einen die Anreize der ausgebeuteten Gruppe zur Produktion des privaten Gutes senkt, zum anderen die Chancen einer erfolgreichen Revolution erhöht. Der Sozialvertrag sieht den Austausch von Sicherheit gegen einen Anteil am privaten Gut vor, das auf hohem Anstrengungsniveau produziert wird. Das Modell ermöglicht es nicht nur, die Bedingungen für Sozialvertragstreue bzw. Ausbeutungsdiktatur herzuleiten, sondern beleuchtet auch den Übergang von einer Regierungsform zur anderen. So leistet es einen Beitrag zur Positiven Konstitutionenökonomik, also dem Forschungsprogramm, das die Entstehung und den Wandel von Verfassungen erklärt.
Keywords: D72; P51; H11; 330; self-enforcing contracts; rule of law; dictatorship; autocracy; Positive Constitutional Economics; Verfassungsökonomik; Autoritäres System; Politische Unruhen; Spieltheorie; Theorie